PENGARUH MODEL COOPERATIVE LEARNING TIPE TPS (THINK PAIR SHARE) TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS 4 SEKOLAH DASAR - Sa'afur Rohmah, Alifa; Eko Retnosari, Ira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research focuses on individual students. The inability of children to collaborate is still commonly observed today, such as when many students prefer to choose their own friends during group activities, making it difficult for them to socialize with others. The Think Pair Share (TPS) type of Cooperative Learning Model is an instructional approach in which students first think independently about the problem posed by the teacher, then discuss it with a partner, and finally share the discussion results with the entire class. This process fosters social interaction and strengthens familiarity among students during group work. The research adopted a quantitative approach and an experimental design. Data were collected by administering a pre-test and a post-test. The statistical analysis, performed with SPSS version 21, included an independent sample T-test which yielded a significance level (2-tailed) of 0.000, a value below the 0.05 threshold. This outcome resulted in the rejection of H₀ and the acceptance of Hₐ. Therefore, it can be concluded that the Think Pair Share (TPS) Cooperative Learning model exerts a significant influence on improving the procedural text writing skills of fourth-grade students.